‘Quo Vadis’ Indonesian Education: Analysis of Moral Disintegration in Educational Institutions - Muhammad Rafliyanto (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to analyze in depth the problems of moral disintegration occurring in Indonesian educational institutions. The question addressed in this study is: What is the role of the Indonesian government in addressing the problems of moral disintegration occurring in Indonesian educational institutions? The objective of this study is to analyze the role of the Indonesian government in addressing the problems of moral disintegration occurring in Indonesian educational institutions. This research uses a literature review approach. The data is analyzed through a critical review of academic literature, previous research results, institutional reports such as KPAI, and the views of moral education experts such as Lawrence Kohlberg, Thomas Lickona, and Narvaez. The results of the study show that moral disintegration is not only caused by internal factors of students but is also influenced by the weakness of the guidance system in schools, the lack of role models among educators, and the imbalance between academic orientation and character development. Additionally, violent behavior by educators indicates that the moral crisis is not only an issue among students but also concerns the personal quality and professionalism of educators. This study confirms that the formation of students' morality requires a systemic approach that involves synergy between schools, families, communities, and the state. The government has a strategic role in strengthening character education policies through the curriculum, teacher training, and supervision of school culture. Therefore, it is necessary to reformulate the educational approach so that it does not merely emphasize cognitive aspects but also fosters ethical and spiritual values in a sustainable manner. This study is expected to serve as a conceptual and reflective reference in formulating the direction of moral education policy in Indonesia in the present and future.